Emotional Intelligence and the Big Five Personality Model of Higher Learning Institutions - Shamsuddin, Noorazzila; Amin, Aziz; Sarina Nik Md Salleh, Nik (International Journal of Engineering and Technology, 2018)
In today's educational environment, especially in institutions of higher learning, the responsibility of lecturers is not solely restricted to teaching and improving the knowledge of students in the classroom, but in fact requires more than that. Academic staffs need strong work ethic and good personality in order to be as a good role model for students. Lecturers, educators, teachers or whatever the term used to call them, is a contributor to the organization's development and excellence. Job descriptions are not only focused on formal job assignments such as lectures, but also require lecturers, for example, to engage in various types of collaboration and help other stakeholders in the organization. In addition, lecturers need to support the social and organizational psychology context and this can be done through organizational citizenship behavior (OCB).Â Â Â